Bentuk dan Strategi Penolakan Anak: Tinjauan Pragmatik Berdasarkan Kedudukan Lawan Tutur - Zuhry, Achmad; Candra Kusuma, Iswahyudi (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2025)
This study describes the forms of expression of rejection by children by looking at the role or position of the interlocutor. This study also looks at the form of sentences pragmatically towards the interlocutor through utterances of rejection by a child. This research uses a qualitative descriptive method by explaining the data obtained through a description or explanation of the meaning of the utterances in the research data. Data collection was carried out using record and note techniques. The results of the study show that there are different forms of refusal in the form of sentences or explicit or implicit refusals depending on the other person. The form of the sentence is declarative which is pragmatically understood by the interlocutor as a form of rejection. The position, distance, and social relations that exist between a child and his interlocutor affect the form of rejection associated with the burden of politeness or the child’s strategy in politeness. The closer the distance or relationship between a child and his interlocutor, the lighter the politeness strategy used by a child.